Efficacy of Spiritual-Religious Interventions on Clinical and Functional Outcomes in Iranian Adults with Mental Disorders/Negative Psychological Symptoms: A Systematic Review of Randomized Controlled Trials - Hassan Farrahi; Fataneh Bakhshi; Hadi Basiri; Fatemeh Amini Khodashahri; Zeynab Haghdoost (Caspian Journal of Health Research)
Background: Studies on the effectiveness of spiritual-religious interventions in mental disorders exist, but the results remain inconsistent or insufficient. Moreover, many of these studies have not employed randomized controlled trial (RCT) methodologies to assess the efficacy of such interventions. Objectives: The present study aimed to review RCTs evaluating the effectiveness of spiritual-religious care-based interventions on clinical and functional outcomes in Iranian adults with mental disorders and negative psychological symptoms. Materials and Methods: A comprehensive search was conducted across Iranian and international scientific databases until 2022. Studies included in this review were required to meet the following criteria: (a) clinical trials, (b) controlled, and (c) randomized, investigating the effectiveness of spiritual-religious care-based interventions in adults aged 18 years and older with mental disorders or negative psychological symptoms. The retrieved studies were independently evaluated by two researchers, and their quality was assessed using the Cochrane Back Review Scale. Results: No statistical analysis of outcomes was performed; instead, a narrative summary was chosen to describe the included studies. A total of 19 studies involving 1383 participants were identified, encompassing various interventions. Most studies indicated that spiritual-religious care had a beneficial and significant impact on increasing the quality of life and spiritual well-being and decreasing the psychological distress of adults with mental disorders and negative psychological symptoms. Conclusion: Spiritual-religious care-based interventions in Iranian adults with mental disorders and negative psychological symptoms were effective in enhancing quality of life and spiritual well-being while reducing depression, anxiety, and hopelessness. These findings suggest that healthcare professionals can utilize such interventions in the Iranian patient population to improve quality of life and alleviate negative psychological symptoms.